Mode-Dependent Effect of Xenon Inhalation on Kainic Acid-Induced Status Epilepticus in Rats - Zhang, Yurong; Zhang, Mengdi; Yu, Jie; Zhu, Wei; Wang, Qiaoyun; Pan, Xiaohong; Gao, Xue; Yang, Jing; Sun, Hongliu (Frontiers in Cellular Neuroscience, 2019)
Previous studies have reported the possible neuroprotective effects of xenon treatment. The purpose of this study was to define the range of effective xenon ratio, most effective xenon ratio, and time-window for intervention in the kainic acid (KA)- induced status epilepticus (SE) rat model. Different ratios of xenon (35% xenon/21% oxygen/44% nitrogen, 50% xenon/21% oxygen/29% nitrogen, and 70% xenon/21% oxygen/9% nitrogen) were used to treat the KA-induced SE. Our results confirmed the anti-seizure role of 50% and 70% xenon mixture, with a stronger effect from the latter. Further, 70% xenon mixture was dispensed at three time points (0 min, 15 min delayed, and 30 min delayed) after KA administration, and the results indicated the anti-seizure effect at all treated time points. The results also established that the neuronal injury, assessed using Fluoro-Jade B staining, in the hippocampus and entorhinal cortex (EC) were reversed by the xenon inhalation and within 30 min after KA administration. Our study, therefore, indicates the appropriate effective xenon ratio and time-window for intervention that can depress seizures. The prevention of neuronal injury and further reversal of the loss of effective control of depress network in the hippocampus and EC may be the mechanisms underlying the anti-seizure effect of xenon.